GESTIÓN DE INNOVACIÓN, CREATIVIDAD Y DESARROLLO - Castillo Maza, Juan (2005)
The nation’s development in globalization’s context is based on creativity of its human beings and permanent innovation of mechanisms of gestion and instruments of business units and organizations in general. The changes in the last ten years experimented by enterprises have been resulted from decisions of known leaders to promote creativity and innovation as development mechanisms. The creativity and innovation necessity in the enterprises is evident, because it lets them to reduce costs, time and resources for production and optimum distribution, it makes planning, organization, direction and control efficient, that is, objectives are achieved which allow enterprises, institutions and any one working on goods and services to obtain optimum results. The creativity, innovation and development are main elements in the business success that benefits consumers, users and citizens.